Analisis Manajemen Badan Kemakmuran Masjid dalam Pengelolaan Pendidikan Keislaman Berbasis Masjid - Usman Usman; Jasmadi Jasmadi; Zamzami Zamzami (Jurnal Ilmiah Guru Madrasah, 2025)
The Mosque Prosperity Agency (BKM) is a mosque management institution that plays a strategic role in promoting the functions of houses of worship, both in terms of worship, social aspects, and community empowerment. This study aims to review the performance of BKM from the perspective of Islamic organisational management, emphasising the principles of trust, consultation (syura), justice, and accountability. The research method used is descriptive qualitative, with data collection techniques including interviews, observation, and documentation studies at several mosques managed by BKM. Data analysis was conducted using an Islamic organisational management approach that included planning, organising, actuating, and controlling, as well as being linked to sharia values. The results of the study show that most BKM have attempted to apply modern management principles, such as work programme preparation, financial management, and organisational structure management. However, its implementation still faces obstacles in the form of a lack of professionalism, weak transparency, and limited human resource capacity. The Islamic organisational management perspective provides a normative framework that can strengthen BKM institutional practices, particularly in maintaining trust, increasing congregational participation through deliberation, and upholding justice in the distribution of mosque activities. This study concludes that the effectiveness of BKM is not only determined by its administrative structure and system, but also by the extent to which Islamic values are internalised in every managerial process. Thus, this study recommends strengthening the Islamic value-based managerial capacity of BKM administrators so that mosques can become centres of worship, education, and sustainable community empowerment